Ruthenium(II) bipyridine complexes: from synthesis and crystal structures to electrochemical and cytotoxicity investigation. Issue 5 (4th March 2017) - Baroud, Afya A.; Mihajlović-Lalić, Ljiljana E.; Gligorijević, Nevenka; Aranđelović, Sandra; Stanković, Dalibor; Radulović, Siniša; Van Hecke, Kristof; Savić, Aleksandar; Grgurić-Šipka, Sanja
Abstract: Complexes1–4, [Ru(L)(bpy)2 ]PF6, where bpy = 2, 2′-bipyridine; HL = 3-methylpyridine-2-carboxylic acid (HL1 ), 6-methylpyridine-2-carboxylic acid (HL2 ), 5-bromopyridine-2-carboxylic acid (HL3 ) and 6-bromopyridine-2-carboxylic acid (HL4 ), were synthesized and characterized. The electrochemical character of the complexes was investigated by cyclic voltammetry revealing two reversible reduction waves in the negative range of potentials, most likely due to a reduction of the bipyridine moiety. Cytotoxicity studies by MTT assay for 72 h of drug action revealed that2–4 exhibited moderate activity in cervical human tumor cells (HeLa). Complex2 exhibited low activity in colon cancer LS-174 cells (180 ± 10), while all complexes were devoid of activity in lung cancer A549 and non-tumor MRC-5 cells, up to 200 μM. Combinational studies of the most active complex2, with pharmacological modulators of cell redox status, L-buthionine-sulfoximine (L-BSO) or N-acetyl-L-cysteine (NAC), showed that when L-BSO potentiated, 2 induced a sub-G1 peak of the cell cycle in the HeLa cell line. UV–vis and cyclic voltammetry were performed in order to investigate the binding mode of2 to DNA and suggested intercalation for the complex–DNA interaction. Abstract :